2013
DOI: 10.1088/0004-637x/774/2/154
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Reconnection at a Solar Coronal Null Point Above a Separatrix Dome

Abstract: Three-dimensional magnetic null points are ubiquitous in the solar corona, and in any generic mixed-polarity magnetic field. We consider magnetic reconnection at an isolated coronal null point, whose fan field lines form a dome structure. We demonstrate using analytical and computational models several features of spine-fan reconnection at such a null, including the fact that substantial magnetic flux transfer from one region of field line connectivity to another can occur. The flux transfer occurs across the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 44 publications
7
99
0
Order By: Relevance
“…Investigations of magnetic field extrapolations have often used the concept of QSL to identity locations in space where the field line mapping changes particularly fast and reconnection therefore may be initiated. A QSL does not need to contain a mathematical discontinuity in the field line mapping, as implied by the presence of 3D null points, while a null point can be seen to be embedded in a QSL region (Pontin et al 2013). Quasi separator layer regions, like null points, fan planes and separator lines, are found to be locations in space where current easily accumulates when the magnetic field configuration is appropriately stressed.…”
Section: Magnetic Topology Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of magnetic field extrapolations have often used the concept of QSL to identity locations in space where the field line mapping changes particularly fast and reconnection therefore may be initiated. A QSL does not need to contain a mathematical discontinuity in the field line mapping, as implied by the presence of 3D null points, while a null point can be seen to be embedded in a QSL region (Pontin et al 2013). Quasi separator layer regions, like null points, fan planes and separator lines, are found to be locations in space where current easily accumulates when the magnetic field configuration is appropriately stressed.…”
Section: Magnetic Topology Evolutionmentioning
confidence: 99%
“…Their global potential field source surface (PFSS) model (which is the only investigation taking into account the large scale magnetic field) suggests, that a QSL related reconnection takes place close to the active region populating the field lines with active region FIP enhanced plasma. These field lines are further required to pass through a second reconnection with a distant 3D null, experiencing a spine-fan reconnection (Priest & Pontin 2009;Pontin et al 2013;Galsgaard & Pontin 2011) process before the plasma finally enters an open field region.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, different regimes of reconnection have been studied, from a kinematic approach to a dynamic approach with the help of numerical simulations. Depending on whether the process takes place at null points (see Parnell et al 1996;Priest & Titov 1996;Pontin, Hornig & Priest 2004, 2005Pontin, Priest & Galsgaard 2013, and references therein for more explanation on the fan, spine reconnection at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S0022377817000034 (a) ( b) FIGURE 2.…”
Section: Magnetic Topology Of Solar Flaresmentioning
confidence: 99%
“…The decoupling of the ions and the electrons are shown in figure 8(b), where the diffusion region is defined differently (with different physical effects) for the ions and the electrons. Studies of small-scale effects therefore include Hall fields (Drake, Shay & Swisdak 2008), anisotropic pressure , electron dynamics and viscosity Hesse, Kuznetsova & Birn 2004;Cai & Li 2008), while reviews of these effects can also be found in Porcelli et al (2002), Shay et al (2004), Büchner (2007.…”
Section: Dissipation Processmentioning
confidence: 99%
“…Because the field component normal to the photosphere in these simulations is held constant, the flux beneath the separatrix dome is a fixed quantity. To preserve it, the amount of flux being opened and closed across the separatrix must be equal at any given time (see also Pontin et al 2013). This type of reconnection is often termed "interchange reconnection."…”
Section: Reconnection Analysismentioning
confidence: 99%